Estimation Of Evapotranspiration Based On Local Meteorological Data, For Penang Island - Natar, Maslina Mohd (2012)
Evapotranspiration (ET) constitute a large portion of hydrological cycle which is stabilizing energy balance at the surface as a consequence of change energy flux between land surface and atmosphere. Usually, rate of evaporation obtain from Meteorological services while data of evapotranspiration is rarely available. In this study, Surface Energy Balance Systems (SEBS) has been utilized to measure turbulent flux and evaporative fraction in order to estimate rate of evapotranspiration using remotely sensed data and meteorological observation. SEBS required three datasets. First data sets is meteorology observation consist of wind speed, air pressure, relative humidity and air temperature.